Clonality and timing of relapsing colorectal cancer metastasis revealed through whole-genome single-cell sequencing. (1st September 2022) - Alves, Joao M.; Prado-López, Sonia; Tomás, Laura; Valecha, Monica; Estévez-Gómez, Nuria; Alvariño, Pilar; Geisel, Dominik; Modest, Dominik Paul; Sauer, Igor M.; Pratschke, Johann; Raschzok, Nathanael; Sers, Christine; et al.
Abstract: Recurrence of tumor cells following local and systemic therapy is a significant hurdle in cancer. Most patients with metastatic colorectal cancer (mCRC) will relapse, despite resection of the metastatic lesions. A better understanding of the evolutionary history of recurrent lesions is required to identify the spatial and temporal patterns of metastatic progression and expose the genetic and evolutionary determinants of therapeutic resistance. With this goal in mind, here we leveraged a unique single-cell whole-genome sequencing dataset from recurrent hepatic lesions of an mCRC patient. Our phylogenetic analysis confirms that the treatment induced a severe demographic bottleneck in the liver metastasis but also that a previously diverged lineage survived this surgery, possibly after migration to a different site in the liver. This lineage evolved very slowly for two years under adjuvant drug therapy and diversified again in a very short period. We identified several non-silent mutations specific to this lineage and inferred a substantial contribution of chemotherapy to the overall, genome-wide mutational burden. All in all, our study suggests that mCRC subclones can migrate locally and evade resection, keep evolving despite rounds of chemotherapy, and re-expand explosively. Highlights: The phylogenetic analysis of single-cells exposes how, where and when malignant cells survive treatment in a personalized manner. The relapse originated from the expansion of a single metastatic lineage that slowly evolved in the liver. More than 500 mutations are specific to the relapse, including four non-silent mutations with no apparent clinical significance. There is a clear contribution of chemotherapy exposure to the overall mutational burden of the relapse.